2019
DOI: 10.1186/s13568-019-0802-9
|View full text |Cite
|
Sign up to set email alerts
|

Bioconversion of curcumin into calebin-A by the endophytic fungus Ovatospora brasiliensis EPE-10 MTCC 25236 associated with Curcuma caesia

Abstract: Calebin-A is a curcuminoid compound reported to be present in Curcuma longa rhizome. The current study was aimed to isolate and characterize calebin-A from Curcuma caesia rhizome and its production through biotransformation approach using endophytic fungus. C. caesia rhizomes of different ages were subjected to analysis in order to investigate the age at which maximum calebin-A content is present. HP-TLC profiles, HPLC retention times and mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…Calebin A does not belong to the larger group of curcuminoids, which are considered the main active compounds found in turmeric [24], but to the small fraction of non-curcuminoides [25]. The content of Calebin A in turmeric extract ranges approximately around 0.001% [23,26]. Previously, Calebin A has been shown to possess anti-cancer properties [27], suppress adipogenesis [28], down-regulate osteoclastogenesis [29] and protect neuronal cells from beta-amyloid insult [22].…”
Section: Introductionmentioning
confidence: 99%
“…Calebin A does not belong to the larger group of curcuminoids, which are considered the main active compounds found in turmeric [24], but to the small fraction of non-curcuminoides [25]. The content of Calebin A in turmeric extract ranges approximately around 0.001% [23,26]. Previously, Calebin A has been shown to possess anti-cancer properties [27], suppress adipogenesis [28], down-regulate osteoclastogenesis [29] and protect neuronal cells from beta-amyloid insult [22].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown the beneficial health effects of these chemicals, but bioavailability remains a concern due to their low solubility in water [ 21 ]. In order to enhance their water solubility and subsequent bioavailability, various approaches including nano-particlization [ 22 ], encapsulation [ 23 ] and bioconversion [ 24 ] have been introduced. It was also reported that emulsion formation of curcumin with oils aid in the bioaccessibility through the lipid digestion and absorption system in the gastrointestinal tract [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The scope of fungal endophytes as whole-cell biotransformation can further be expanded for generating alternative sources of limited biologically active natural compounds. This was exemplified by the work of Majeed et al (2019) who suggested the novel bioconversion route for the production of calebin-A from curcumin assisted by endophytic fungus, Ovatospora brasiliensis EPE-10 MTCC 25236, isolated from the rhizomes of Curcuma caesia. In contrast to whole-cell biotransformation, isolated enzymes have more potential in single-step catalysis than conventional chemical approaches.…”
Section: Biotransformation Reactions Mediated By Endophytic Fungimentioning
confidence: 99%